2021
DOI: 10.1007/s10825-021-01804-6
|View full text |Cite
|
Sign up to set email alerts
|

Master equations for Wigner functions with spontaneous collapse and their relation to thermodynamic irreversibility

Abstract: Wigner functions, allowing for a reformulation of quantum mechanics in phase space, are of central importance for the study of the quantum-classical transition. A full understanding of the quantum-classical transition, however, also requires an explanation for the absence of macroscopic superpositions to solve the quantum measurement problem. Stochastic reformulations of quantum mechanics based on spontaneous collapses of the wavefunction are a popular approach to this issue. In this article, we derive the dyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 140 publications
0
11
0
Order By: Relevance
“…Albert (1994a,b) argues that the GRW collapses will bring a system starting in an "abnormal" initial state 3 into a state that leads to a normal thermodynamic time evolution. However, te Vrugt et al (2021b) have found no such effect in their simulations.…”
Section: Probabilitymentioning
confidence: 86%
See 3 more Smart Citations
“…Albert (1994a,b) argues that the GRW collapses will bring a system starting in an "abnormal" initial state 3 into a state that leads to a normal thermodynamic time evolution. However, te Vrugt et al (2021b) have found no such effect in their simulations.…”
Section: Probabilitymentioning
confidence: 86%
“…Broadly speaking, there are (at least) three ways around this issue. The first one (not considered here, but in a certain variant refuted in te Vrugt et al (2021b)) is to argue that the microscopic dynamics of a closed system is not actually Hamiltonian. The second one is that external perturbations destroy correlations and thereby lead to an equilibrium form for ρ (interventionism, see Ridderbos and Redhead (1998)).…”
Section: Grabert's Projection Operator Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…Since GRW theory involves objective stochasticity, one would then have a straightforward explanation for the existence of objective probabilities in statistical mechanics. However, recent computer experiments by te Vrugt et al (2021b) indicate that Albert's suggestion is not successful as an explanation of thermodynamic irreversibility even if GRW theory is true. Albert (1994a, b) argues that the GRW collapses will bring a system starting in an "abnormal" initial state 3 into a state that leads to a normal thermodynamic time evolution.…”
Section: Probabilitymentioning
confidence: 99%